The Effectiveness of Electronic Cigarette on Smoking Cessation in Adult Smokers: A Systematic review and Meta-analysis - Pudkasam, Supa; Liangruenrom, Nucharapon; Poonruksa, Siriporn (Scholar: Human Sciences, 2025)
Purpose: The study aims to examine the effect size of e-cigarettes on smoking cessation in adult smokers with subgroups analysis based on their intention to quit. Research design, data and methodology: Quantitative studies that assessed the effect size of e-cigarettes on smoking cessation in adult smokers were searched from four databases. The included articles were imported into EndNote X8 and screened based on eligibility criteria. The data extraction was completed using Microsoft Excel. Pooled effect size (odds ratio) was used to analyze the fixed effect model or random effect model depending on the similarity of recruited studies. Results: The overall odds ratio among six recruited randomized controlled trials (RCTs), eight longitudinal and two cross-sectional studies were 0.88 (95% CI: 0.74–1.05), 1.01 (95% CI: 0.65–1.59) and 0.75 (95% CI: 0.16–3.46), respectively. In the subgroup analysis of participants who initially intended to quit, the odds ratio for smoking cessation associated with e-cigarette use were 0.88 (95% CI: 0.71–1.04) in RCTs, 1.08 (95% CI: 0.49–2.39) in cohort longitudinal studies, and 1.42 (95% CI: 0.81-2.49) in cross-sectional studies. Conclusions: The study has not found a significant effect of e-cigarettes on quitting smoking. Smoking cessation strategies should be more focused in future studies.